KONTRIBUSI KEMAMPUAN AWAL DAN PERSEPSI SISWA TENTANG KUALITAS PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS IMERSI : Studi pada Kelas Imersi Mata Pelajaran Ekonomi Kelas X SMAN 1 Cawas dan SMAN 2 Klaten - Astutik, Sri (2012)
This research is based on the understanding of various factors which determine students' success. One of those factors is students itsef as an instruction subject, that greatly affects in attaining the learning outcome.The general objective of this research is to obtain an empirical description of factors that affect learning outcome in immersion class.The spesifics objectives of this study are:1)to measure the contribution of the students' prior achievement towards to learning outcome in immersion class.2)obtaining the contribution description of students' perception about the quality of the instruction in immersion class towards to the achievement.3)obtaining the contribution description of the prior achievement and students'perception about the quality of the instruction in immersion class toward to the learning achievement of the economics. This is an descriptive quantitave research with survey method.Data of this study are studens' achievement and students' opinion. In this research students takes part as respondent. The research findings show:1) variabel of the prior achievement has negative contribution to the achievement as -0.149, 2)students' percepeion about the quality of the instruction in immersion class positively contribute as 0.19 to the achievement.3). prior achievement and student's perception about the quality of the instruction together contribute to the students' achievement. Recommendation are:1) to school: a) implement a further internal policy after analyzing of the influencing component of the prior achievement, such as determinng standart to decide the position of each school; b).giving the teacher equal opportunity to build up their capcity.c) implementing co teaching among the teachers, and expernal party (native speakers who master subject matter. 2) to teacher: a) teachers must build up their foreign language literacy and skill practise b) teachers involve the students to determine learning material in order to accomadate students' need,c) teacher must have self-awareness to coordinate each other.3) to same field researcher must examine thoroughly the other factors which more dominantly affect to learning results.